ROLE OF LCAT AND HDL IN RELATION TO OXIDATIVE STRESS IN MYOCARDIAL INFARCTION AND ISCHEMIC HEART DISEASE - SHANKAR MANOHAR PAWAR,; E PRABHAKAR REDDY,; CHITRA NETARE,; T. MOHANA LAKSHMI, (The Bioscan, 2011)
Lipids are the most susceptible for free radicals attack; it has been found that there is a significant correlation between oxidative stress and HDL cholesterol and LCAT activity. Decrease in ratio between LCAT and HDL to lipid peroxidation has been a diagnostic marker for management of MI and IHD and will be a good marker.